2001
DOI: 10.1097/00004479-200107000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Health Status Assessments Using the Veterans SF-12 and SF-36: Methods for Evaluating Outcomes in the Veterans Health Administration

Abstract: This article describes a study in which the administration of two health surveys, the Veterans SF-36 and SF-12, by telephone and mail-out was used to assess the differences in the health surveys' costs and scores by mode of administration and determine which mode was cost-efficient. The study employed a crossover design: after 12 unsuccessful attempts to contact patients by telephone, the patients were administered the survey by mail, and after 2 unsuccessful mail-outs, up to three attempts were made to interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(117 citation statements)
references
References 3 publications
1
116
0
Order By: Relevance
“…These instruments were adapted for use in veteran samples by increasing the number of response options, resulting in fewer floor and ceiling effects, increased reliability, and greater explanatory power (Kazis et al, 2004). They are among the most widely used functional status measures in the world and have been shown to be reliable and valid (Jones et al, 2001). …”
Section: Mental Health Functioningmentioning
confidence: 99%
“…These instruments were adapted for use in veteran samples by increasing the number of response options, resulting in fewer floor and ceiling effects, increased reliability, and greater explanatory power (Kazis et al, 2004). They are among the most widely used functional status measures in the world and have been shown to be reliable and valid (Jones et al, 2001). …”
Section: Mental Health Functioningmentioning
confidence: 99%
“…Seventeen studies 104,[111][112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] published between 1994 and 2003 used SF-36. Not all studies reported all subscales.…”
Section: Meta-analysis Of Short Form Questionnaire-36 Itemsmentioning
confidence: 99%
“…The impact of the different modes of using SF-36 was assessed using weighted pooled measures of agreement for within-subject comparisons and random-effects meta-analysis for between-subject comparison. There were seven studies 104,111,112,[114][115][116][117] that provided betweensubject comparisons only, eight studies [119][120][121][122][123][124][125][126] that provided within-subject comparisons only and two studies 113,118 that contributed data to both analyses. Table 15 summarises the information available from each study.…”
Section: Meta-analysis Of Short Form Questionnaire-36 Itemsmentioning
confidence: 99%
“…Standardized instruments include the PHQ (2,8,9), used to assess major depressive syndrome, panic syndrome, other anxiety syndrome, bulimia nervosa, alcohol abuse, and bingeeating disorders (overall accuracy Z 0.85; sensitivity Z 0.75; specificity Z 0.90), as well as specific conditions such as major depressive disorder found to be highly sensitive and specific (sensitivity Z 0.93; specificity Z 0.89) (12) and panic disorder found to be highly sensitive but moderately specific (sensitivity Z 1.00; specificity Z 0.63) (13). The SF-36V was also included (6, 7) to define 8 components to assess physical functioning, role limitations caused by physical problems, bodily pain, general health, vitality, social functioning, role limitations caused by emotional problems, and mental health and has been found to have high internal consistency across all 8 domains in a military population (14). These 8 health concepts constitute the component summary measures Physical Component Summary (PCS) and Mental Component Summary (MCS) (15)(16)(17) Components of the National Health Survey of Gulf War Era Veterans and Their Families were included to assess wartime exposures (18,19).…”
Section: Questionnaire Datamentioning
confidence: 99%